Modelling Human Channelopathies Using Induced Pluripotent Stem Cells: A Comprehensive Review - Martin Müller; Thomas Seufferlein; Anett Illing; Jörg Homann (Hindawi Limited, 2013)
The generation of induced pluripotent stem cells (iPS cells) has pioneered the field of regenerative medicine and developmental biology. They can be generated by overexpression of a defined set of transcription factors in somatic cells derived from easily accessible tissues such as skin or plucked hair or even human urine. In case of applying this tool to patients who are classified into a disease group, it enables the generation of a disease- and patient-specific research platform. iPS cells have proven a significant tool to elucidate pathophysiological mechanisms in various diseases such as diabetes, blood disorders, defined neurological disorders, and genetic liver disease. One of the first successfully modelled human diseases was long QT syndrome, an inherited cardiac channelopathy which causes potentially fatal cardiac arrhythmia. This review summarizes the efforts of reprogramming various types of long QT syndrome and discusses the potential underlying mechanisms and their application.